2017
DOI: 10.6000/1929-6037.2017.06.02.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization of APA Microcapsules by Parallel-Plate Compression

Abstract: We produced microcapsules of alginate-poly(L)lysine-alginate (APA)with diameters on the order of 10 µm. To characterize their mechanical properties, we conducted an experiment on the parallel-plate compression of a microcapsule and modeled its deformation. In the modeling task, the microcapsule was assumed to be a spherical liquidfilled elastic membrane with negligible bending stiffness and permeability. The membrane thickness was estimated by applying Reissner's linear elastic theory to the experimental force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Yamaguchi group reported that Young's modulus of the APA membrane could be tuned by changing the thickness of APA membrane coating. [51] Sun et al reported that the APA membrane thickness increases with the increase of the concentration of sodium alginate, calcium solution, and PLL, the reaction time with PLL, and the molecular weight of PLL. [52] On the other hand, grafting functional ligands onto APA microcapsules can be employed to manipulate MSC differentiation.…”
Section: Osteogenesis In the Compartmentalized And Vascularized Osteo...mentioning
confidence: 99%
“…Yamaguchi group reported that Young's modulus of the APA membrane could be tuned by changing the thickness of APA membrane coating. [51] Sun et al reported that the APA membrane thickness increases with the increase of the concentration of sodium alginate, calcium solution, and PLL, the reaction time with PLL, and the molecular weight of PLL. [52] On the other hand, grafting functional ligands onto APA microcapsules can be employed to manipulate MSC differentiation.…”
Section: Osteogenesis In the Compartmentalized And Vascularized Osteo...mentioning
confidence: 99%